Raman Fingerprints of π-Electron Delocalization in Polythiophene-Based Insulated Molecular Wires - Mosca, Sara; Milani, Alberto; Castiglioni, Chiara; Hernández-Jolín, Víctor; Meseguer, Cristóbal; López-Navarrete, Juan Teodomiro; Zhao, Chunhui; Sugiyasu, Kazunori; Ruiz-Delgado, María del Carmen (ACS, 2022)
Insulated polythiophenes with a polyrotaxane-like 3D architecture have shown excellent intrawire hole mobility, allowing their use in interesting optoelectronic applications. This is due to the isolation of the π-conjugated backbones that warrants for stabilization of the quasi-planar conformation of the polythiophene core and prevents electronic communication between adjacent chains. Thus, polythiophene-based insulated molecular wires (IMWs) constitute ideal test-beds to evaluate the structural changes within the conjugated polymer chain, such as intrachain conformation and π-electron delocalization. Here, we investigate the structure and spectroscopic response of fully and partially insulated polythiophene-based IMWs. An experimental investigation of Raman spectra supported by density functional theory (DFT) calculations allows us to give a detailed interpretation of intramolecular interactions, highlighting differences in π-electron conjugation revealed by the presence of an intensity transfer between the two main Raman modes associated with the C═C/C–C stretching vibrations. This study proves the sensitivity of Raman spectroscopy as a technique to monitor structural changes in self-encapsulated conjugated polymers.
Keywords: Oligómeros (Polímeros); Copolymers; Defects; Oligomers; Polymers